Volatility of Short-term Capital Flows and Private Investment in Emerging Markets. - Demir, Firat (Journal of Development Studies, 2009)
Using micro-level panel data, the paper analyses the impacts of short-term capital flow volatility on new fixed investment spending of publicly traded real sector firms in three major emerging markets - Argentina, Mexico and Turkey. The empirical results, including sensitivity tests, suggest that increasing volatility of capital inflows has an economically and statistically significant negative effect on new investment spending of private firms. Accordingly, a 10 per cent increase in capital flow volatility reduces fixed investment spending in the range of 1-1.7, 2.3-15, and 1 per cent in Argentina, Mexico and Turkey respectively.